Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

-2z+3-z=□-4z+2
please give me the answer


Sagot :

Answer: z=-1

Step-by-step explanation:

[tex]\displaystyle \rm -2z+3-z=-4z+2 \\\\ -3z+3=-4z+2 \\\\ 4z-3z=-3+2 \\\\ \underline{z=-1 \ \ \ \ } \\\\[/tex]

[tex]\large{\rm{\underline{\underline{Answer:}}}}[/tex]

Given to solve: -2z+3-z = -4z+2

⇛ -3z + 3 = -4z + 2

⇛ -3z + 4z = 2 - 3

z = -1

Required value of z is -1. The steps we followed are: We shifted z to a single side and other numbers to other side. Then we equated to get the result.